Pancasila dan PAI sebagai Landasan Normatif Hubungan Industrial melalui Islamic Sociological Jurisprudence : Pancasila and Islamic Education as Normative Foundations of Industrial Relations: An Islamic Sociological Jurisprudence Perspective - Yahya Fadhlullah Murtaja; Muhammad Adip Solikin; Faiq Gibran Abdullah; Ahmad Muhammad Mustain Nasoha (Litera Academica Publishing, 2026)
This article critically examines the normative construction of industrial relations in Indonesia by positioning Pancasila and Islamic Religious Education as ethical-juridical foundations within the framework of Islamic Sociological Jurisprudence Theory. Conceptually, Pancasila as a staatsfundamentalnorm functions as a rechtsidee that aspires to the realization of social justice; however, in practice, industrial law still exhibits a tendency toward legal-formalism, often neglecting substantive justice and the balance of relations between workers and employers. On the other hand, the values of Islamic Religious Education, such as ‘adl (justice), maslahah (public interest), and tawazun (balance), have not been systematically integrated into the design of industrial relations policies. This study employs a qualitative approach using a normative-doctrinal analysis method enriched by a sociological legal perspective to identify the gap between law in books and law in action. The findings reveal a disjunction between positive legal norms and the social reality of industrial relations, which remains characterized by structural inequality, weak bargaining power of workers, and the dominance of market economic logic. Through the framework of Islamic Sociological Jurisprudence, law is repositioned as an instrument of social transformation (law as a tool of social engineering) oriented toward substantive justice and collective welfare. The implications of this study underscore the urgency of reformulating industrial law through an interdisciplinary integration of Pancasila values and Islamic principles to establish an industrial relations system that not only ensures legal certainty but also delivers genuine, humanistic, and sustainable social justice amid the dynamics of global capitalism.